„Biblioteka” – rocznik. Znaczenie czasopisma - Chachlikowska, Aldona (My University, 2015)
Artykuł jest omówieniem tradycji i znaczenia rocznika „Biblioteka” wydawanego od 1997 roku przez Bibliotekę Uniwersytecką w Poznaniu. Tekst potraktowany został przede wszystkim jako uzupełnienie wcześniej przygotowanego i opublikowanego materiału, przedstawiającego dzieje rocznika do 2009 roku , dlatego też obecnie nacisk został położony na zmiany w prezentowanej problematyce w odniesieniu do lat wcześniejszych, porównania i oczekiwania oraz preferencje redakcji, które dokonały się w latach 2010 – 2014. Zamieszczono też analizę wyświetleń dotyczących „Biblioteki” co pozwala ocenić zainteresowanie czytelników rocznikiem.

This article is a review and discussion of the tradition and the importance of the periodical publication "Biblioteka" that has been published annually by Poznań University Library since 1997. The present investigation is a continuation and extension of an earlier published investigation of the author in which the history of the title until the year 2009 is presented [1]. The current review deals primarily with and focuses on the changes in the scope, insights and perspectives of the issues and problems involved in developing and managing libraries and library collections in view of those that prevailed over the previous years. The article also provides the reader with a discussion on the comparisons, expectations and preferences in the selection of the content for the publication by the editorial board of "Biblioteka" in the years spanning 2010 – 2014. In addition, an analysis of page hits and searches on the web-based version of the title is discussed, which makes it possible to determine and evaluate particular interests of its online readers.